Trajectories of home nursing use for older women in Melbourne, Australia: 2006‐2015. (15th October 2019) - Dickins, Marissa; Joe, Angela; Enticott, Joanne; Ogrin, Rajna; Lowthian, Judy
Abstract: Objective: To profile changes in older women accessing home nursing between 2006 and 2015, focussing on living circumstances. Methods: Data pertaining to Australian women aged 55+ who accessed a home nursing service between 2006 and 2015 were analysed, stratified by living status. Comparisons were made between the years 2006 and 2015; rates and relative rates of use per 1000 clients were calculated. Results: Fewer women lived alone in 2015 compared with 2006. Women were older, less likely to be born in Australia, speak English at home, had more diagnoses and higher average Charlson Comorbidity Index scores in 2015. Relative rates of service use for older women living with others increased slightly over the 10 years, while decreasing by 13% for those living alone. Conclusion: Women using home nursing services are older than previously, more medically complex, more likely to be born from countries other than Australia and speak a preferred language other than English.